Evaluation of job satisfaction as a mediator: Exploring the relationship between workload, career growth, social support supervisory and talent retention in the oil and gas industry in Malaysia - Salleh, Rohani; Sonia Lohana, Sonia Lohana; Vicky Kumar, Vicky Kumar; Siti Nooriza, Siti Nooriza (Elsevier, 2024)
People may feel contented or unsatisfied with their employment, a complex state known as job satisfaction. Assessing employee effectiveness and productivity is crucial. The oil and gas sector plays a significant role in national development and economic strengthening. The industry is known for its challenging nature and goals, often resulting in a high turnover rate and frequent job transitions among employees. Such issues present a significant hurdle for organizations in this industry. This study investigates the impact of workload, career advancement, supervisor support, and talent retention on job satisfaction in the oil and gas industry. Through convenience sampling, 200 surveys were distributed, of which 155 were successfully collected, resulting in an 89 % response rate. The responses varied across different demographic and functional roles within the industry. The data was analyzed using Smart-PLS 4. The findings revealed that each independent variable had a positive and statistically significant effect on job satisfaction. Specifically, talent retention emerged as the most influential predictor of job satisfaction. The results suggest that organizations should prioritize effective talent management strategies to enhance the satisfaction and retention of their employees in the oil and gas industry.